THE CHARISMATIC RENEWAL MOVEMENT AND ITS ROLE IN EDUCATION - Alva, Reginald (Asian Horizons, 2014)
The Second Vatican Council (1962-1965) envisaged the overall renewal of the Catholic Church. The Charismatic Renewal Movement (CCRM), which began in 1967, considers itself as the fruit of the prayer of the Council. CCRM has indeed touched the lives of millions of people. It is estimated that around 12% of the global Catholics are affiliated to various CCRM prayer groups. The primary aim of CCRM is spiritual renewal. It encourages the faithful to spend more time in prayer, read scriptures, aim to live a holy life and enjoy fellowship within a community. In this paper, we shall study the contributions of the Charismatic Movement in the renewal of the Church especially for those involved in education. We shall consider these questions in the light of the documents of the Magisterium and theologians regarding Renewal Movements．In addition, we shall study some actual cases to assess the contributions of the Charismatic Movement for those involved in the field of education in Catholic institutes.